2022
DOI: 10.1097/tp.0000000000004289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Older Donor Age on Recipient and Graft Survival After LDLT: The US Experience

Abstract: Background. The impact of selecting older donors for living donor liver transplantation (LDLT) in the United States is incompletely studied, particularly in light of the recent expansion of LDLT nationally. Methods. Adult LDLTs from January 01, 2005 to December 31, 2019 were identified using the United Network for Organ Sharing database. Multivariable Cox models evaluated living donor (LD) age as a predictor of LDLT recipient and graft survival. The impact of increasing donor age on recipient outcomes was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…in their study using UNOS data 25 . The authors found that living donors aged ≥50y were associated with an adjusted hazard ratio of 1.49 for recipient survival and 1.61 for graft survival when compared to younger living donors aged 18–29 years ( p = .012 and p ≤ .001, respectively) 25 . More importantly, increasing donor age (per 10‐year increase) had a more severe impact on graft and patient survival after LDLT than after DDLT 25 .…”
Section: Discussionmentioning
confidence: 99%
“…in their study using UNOS data 25 . The authors found that living donors aged ≥50y were associated with an adjusted hazard ratio of 1.49 for recipient survival and 1.61 for graft survival when compared to younger living donors aged 18–29 years ( p = .012 and p ≤ .001, respectively) 25 . More importantly, increasing donor age (per 10‐year increase) had a more severe impact on graft and patient survival after LDLT than after DDLT 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, in medical statistics, the criterion for older age is commonly set at 60 or 65 years. However, in the case of liver donors, a different cut‐off, such as 50 or 55 years, may be applied 11,12 . Therefore, we also used the age of 50 as a criterion in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the case of liver donors, a different cut-off, such as 50 or 55 years, may be applied. 11,12 Therefore, we also used the age of 50 as a criterion in our analyses. Donors were divided into three groups: PLDRH, donor age ≥50…”
Section: Patients and Datamentioning
confidence: 99%
“…[32] The donor age is strongly associated with EAD after LDLT in the studies by Ikegami et al and Pompeselli et al [8,11] In a study enrolling 3539 LDLTs at 65 transplant centers, LD age ≥ 50 years was associated with an adjusted HR of 1.49 (p 0.012) for recipients and 1.61 (p 0.001) for graft survival, respectively (vs. donors aged 18-29 y). [33] The chances of encountering steatosis and subclinical inflammation or fibrosis increase with the older donors' grafts. Such grafts are less resilient, more prone to ischemia and the shear stress injury caused by portal hyperperfusion, and have impaired regenerative ability.…”
Section: Donor Agementioning
confidence: 99%
“…Although the cutoff age associated with safe outcomes in LDLT is enigmatic, experts strongly recommend using grafts from donors younger than 45 years 32 . The donor age is strongly associated with EAD after LDLT in the studies by Ikegami et al and Pompeselli et al 8,11 In a study enrolling 3539 LDLTs at 65 transplant centers, LD age ≥ 50 years was associated with an adjusted HR of 1.49 ( p 0.012) for recipients and 1.61 ( p 0.001) for graft survival, respectively (vs. donors aged 18–29 y) 33 . The chances of encountering steatosis and subclinical inflammation or fibrosis increase with the older donors’ grafts.…”
Section: Introductionmentioning
confidence: 96%